91.8k views
5 votes
Solve for the unknown variable in each equation using an algebraic method(undoing or rewriting)

I need to know how to do it, not the answer, just need to learn how to do it show work and steps please

Solve for the unknown variable in each equation using an algebraic method(undoing-example-1

1 Answer

1 vote

Answer:

a. x=2√3+3 and x = - 2√3 +3

b. x=29.5

c. x=2/3, x= - 2

d. x=25

Explanation:

a). -2(x-3)² +5 = - 19

- 2(x-3)² = -19 - 5

- 2(x-3)² = - 24

(x-3)² = 12

x-3 = √12 and x-3 = -√12

x-3 =2√3 and x-3= -2√3

x=2√3+3 and x = - 2√3 +3

b)


(√(2x+5) )/(4) +1=3\\\\\\(√(2x+5) )/(4) =2\\√(2x+5) =8\\\\(√(2x+5) )^(2)=8^(2)\\2x+5=64\\2x= 59\\x=29.5

c)

-5|3x+2| - 4 = -24

-5|3x + 2| = - 20

|3x +2| = 4

3x+2=4 or - (3x+2)=4

3x=2 or 3x+2 = - 4

x=2/3 or 3x = - 6, x= -2

d)


5\sqrt[3]{x+2} -7=8\\\\5\sqrt[3]{x+2} =15\\\\\sqrt[3]{x+2} =3\\x+2 = 3^(3)\\x+2=27\\x=25

User Nicolas Busca
by
4.8k points